Project-Based Indonesian Language Course Innovation to Improve Student's Critical Thinking - Fitriani Lubis; Achmad Yuhdi; Atika Wasilah; Amayra Tannoubi (STKIP Singkawang, 2024)
This research aims to develop and assess the feasibility of project-based Indonesian language textbooks in enhancing critical thinking among Medan State University students. Following the 4-D model of Research & Development, the process involves analysis, textbook design, material development, and dissemination. Needs analysis includes front-end and material design analyses to formulate learning objectives. The design stage entails compiling project-based learning materials, selecting media, and designing the book's specifications. In the development stage, textbooks are produced and validated by experts, with validation results exceeding 87% for both material and media. Dissemination involves distributing the textbooks to students to test practicality, resulting in a practicality test score of 87.74%. Validation and implementation scores indicate